2006
DOI: 10.1177/000348940611500904
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mitomycin C on the Size of Antrostomy after Endoscopic Sinus Surgery

Abstract: Topical MMC application may have a short-term effect in maintaining the patency of the antrostomy site. However, it does not seem to improve the relative size over an extended period of time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 29 publications
0
21
0
1
Order By: Relevance
“…It was finally reported that single dose inraoperative MMC did not produce any difference compared to control side in frontal recess narrowing [20]. Finally, in the study of Kim et al [11], measuring the narrowing of maxillary sinus ostium enlarged after ESS at first, third and sixth months, it was reported that topical MMC decreased ostium narrowing in a statistically significant manner only in first month and that no difference was established at third and sixth months.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…It was finally reported that single dose inraoperative MMC did not produce any difference compared to control side in frontal recess narrowing [20]. Finally, in the study of Kim et al [11], measuring the narrowing of maxillary sinus ostium enlarged after ESS at first, third and sixth months, it was reported that topical MMC decreased ostium narrowing in a statistically significant manner only in first month and that no difference was established at third and sixth months.…”
Section: Discussionmentioning
confidence: 95%
“…In the study of Park et al [18], 0.4 and 1 mg/ml concentrations were compared, with no significant difference between them. In clinical studies, concentrations of 0.4 and 0.5 mg/ml were used [11,19,20]. In the present study, MMC was applied at the concentration of 0.6 mg/ml.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Also, mucociliary clearance of nasal mucosa was found to be unaffected by application of MMC. 20 Subconjunctival MMC injection (0.2 mg/ml) has been used in the treatment of ocular cicatricial pemphigoid without any complications. 21 Recently, submucosal injection of MMC has been used for esophageal strictures without any complications and recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous clinical and basic science studies have pointed to the possible beneficial effects from long-lasting application of MMC. [15][16][17][18][19][20][21] With the aim of achieving higher drug concentration and long-lasting biologic effect, the authors devised a technique of intramucosal injection of MMC in a circumostial fashion at 4 points during DCR. The purpose of present study was to evaluate the safety and efficacy of this new technique in DCR and to evaluate its outcomes.…”
mentioning
confidence: 99%